Faith and Fiction: Preaching Eco-theology through Literature - Rahmat Setiawan; Eliasanti Agustina; Amiruddin Hadi Wibowo; Fifi Novianty (UIN Siber Syekh Nurjati Cirebon, 2025)
This research aims to reveal how literature lecturers communicate eco-theological values through the teaching of literature, as well as identify the obstacles. This type of research is qualitative, with a narrative approach. The main data were taken from in-depth interviews with literature lecturers. The data analysis technique used in this research is thematic analysis with a hermeneutic approach. Data validity uses triangulation of data sources, member checking, and critical reflection from the researcher. The results showed that: 1) eco-theological becomes a theoretical reflection on the approach used by the speakers; 2) literary works can act as ecological and spiritual preaching spaces; 3) insignificant ecological literacy, curriculum limitations, and students’ unpreparedness become structural and cultural challenges in literary education with an eco-theological perspective); and 4) the need for curriculum reformulation in literature to improve the eco-theological approach. In this pivotal point, teaching can be seen as da’wah and da’wah is not merely about religiosity in orthodox perception.